PENGARUH KOMPENSASI, MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR DINAS LINGKUNGAN HIDUP KOTA SEMARANG - Pantunnisa Ayu Safitri, 15.05.51.0161; ., Muhaimin (Students' Journal of Economic and Management, 2019)
This research was carried out at the Semarang City Environmental Agency to study and analyze the effect of compensation, motivation and job satisfaction on employee performance. The population in this study amounted to 138 employees, and method of data collection use a questionnaires with a total sample of 60 respondents. Data analysis techniques used include validity test, reliability test with alpha coefficient (Alpha Crobach), multiple regression analysis, t test to test and prove the research hypothesis. The test results obtained that compensation has a positive and significant influence on employee performance. motivation has a positive but not significant effect on employee performance. Job satisfaction has a significant positive effect on employee performance